Vaccine hesitancy in Singapore: public trust and socio-cultural beliefs 1819-1962 - Tan, Yi Heng (Nanyang Technological University, 2025)
Historically, anti-vaccination movements have existed since the advent of the first vaccine in 1796, namely the smallpox vaccine that was conceptualised scientifically by Edward Jenner. The recent COVID-19 Pandemic has cast a spotlight on anti-vaccination and vaccine hesitancy. In Singapore, the image of a population accepting of vaccines is well supported by high vaccination rates stemming from compulsory vaccination and a strong national childhood immunisation program. Despite the high vaccination rates at the start of the pandemic, uptake of COVID booster shots otherwise known as updated COVID vaccines has decreased significantly. Through historical sources and examining past vaccination campaigns in Singapore, this thesis aims to highlight the existence of vaccine hesitancy in this nation and how vaccine hesitancy is not a novel phenomenon observed in the country. This paper encourages a closer look at vaccine hesitancy in Singapore’s history and highlight factors that have caused vaccine hesitancy and negative sentiment towards vaccination in Singapore’s history. Additionally, this paper aims to draw attention to how the way in which vaccination campaigns are carried out can affect the way vaccination is perceived and highlight how the lack of public trust in government policies can result in hesitation towards vaccination.